2018
DOI: 10.1016/j.pmedr.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in BMI, obesity, and exercise frequency in a large veteran service organization: A secondary analysis of new veteran member surveys from Team Red, White & Blue

Abstract: The purpose of the present study was to examine regional differences in average self-reported BMI, obesity prevalence, and frequent exercise (FE) among members of Team Red, White, and Blue (Team RWB) – a military veteran service organization founded to increase physical activity in veterans. A total of 10,015 military veterans participated in a needs assessment conducted by Team RWB between December 2014 and August 2016. Multivariate regression analysis with bootstrapped coefficients revealed that: BMI was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…For example, in their study of obesity prevalence among U.S. service members and Veteran, Rush et al (38) reported obesity rates of 35 and 26% in male and female Veterans, respectively. Similar findings were reported by McDaniel et al (32) in their study of regional differences in BMI and physical activity among U.S. Veterans, in which 33.4% of men and 22.8% of women were classified as obese.…”
Section: Discussionsupporting
confidence: 90%
“…For example, in their study of obesity prevalence among U.S. service members and Veteran, Rush et al (38) reported obesity rates of 35 and 26% in male and female Veterans, respectively. Similar findings were reported by McDaniel et al (32) in their study of regional differences in BMI and physical activity among U.S. Veterans, in which 33.4% of men and 22.8% of women were classified as obese.…”
Section: Discussionsupporting
confidence: 90%
“…Our study of veterans coincides with other studies which have shown (a) that veterans have higher rates of chronic disease than nonveterans 20 and (b) that the distribution of chronic disease varies by geographic location. 21,22 Specifically, as we found in our study, areas that are less urbanized are more likely to have higher prevalence rates of chronic disease than areas that are highly urbanized. However, our study advances the literature in that we examine veteran-nonveteran differences in chronic disease prevalence by geographic location, instead of examining these differences only in the national aggregate or by only looking at veterans in isolation.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, cigarette smoking cessation among military veterans may be aided by veteran service organizations, such as The Mission Continues and Team Red, White, and Blue. These veteran service organizations exist to help veterans reintegrate into civilian society by providing social connection opportunities and encouraging a healthy lifestyle, among other things, following military service 8,9 . These veteran service organizations maintain chapters in many states in the United States.…”
Section: Discussionmentioning
confidence: 99%